S_vegetation_vascular_plant_abundance ... - Virve.Ravolainen@Npolar.No (NPI, 2025)
Abundance of vascular plants measured using point intercept frequency. The datasets contains point frequency data (which can be converted to biomass estimates) of the following functional groups and species: * Salix polaris * Bistorta vivipara * Dryas octopetala * Grasses * Oxyria digyna * Sedges and rushes * Small forbs The dataset includes three different types of files and all files (except the readme) are saved as ;-separated txt-files: One data file per year (_YEAR.txt). One coordinate file with coordinates of all sites included in the dataset (_coordinates.txt). One auxiliary file with information about which sites are included in the dataset and when (_aux.txt). The dataset is under embargo, with new datasets uploaded on December 31st, two years after being collected. Older versions of the dataset are publicly available for download. Note that from 2021, the vegetation type previously called dryas heath is now named dryas ridge. This version will be published 31.12.2025, and includes data from ...